Atlantic Salmon (Salmo salar) bacterial and viral innate immune responses are not impaired by florfenicol or tetracycline administration. Issue 123 (April 2022) - Zanuzzo, Fábio S.; Sandrelli, Rebeccah M.; Peroni, Ellen de Fátima C.; Hall, Jennifer R.; Rise, Matthew L.; Gamperl, Anthony K.
Abstract: Antibiotics are used to treat bacterial infections in fish aquaculture, and these drugs can interact with immune cells/the immune system and potentially leave fish vulnerable to viral, fungal, parasitic, or other bacterial infections. However, the effects of antibiotics on fish immunity have largely been overlooked by the aquaculture industry. We tested, at 12 and 20 °C, whether tetracycline and florfenicol (the most commonly used antibiotics in commercial aquaculture), affected the Atlantic salmon's capacity to respond to bacterial or viral stimulation. Atlantic salmon were acclimated to 12 or 20 °C and fed with tetracycline or florfenicol (100 and 10 mg kg of body weight −1 day −1, respectively) medicated feed for 15 or 10 days, respectively. Thereafter, we evaluated their immune function prior to, and after, an intraperitoneal injection of Forte Micro (containing inactivated cultures of Aeromonas salmonicida, Vibrio anguillarum, Vibrio ordalii and Vibrio salmonicida ) or the viral mimic polyriboinosinic polyribocytidylic acid (pIC). We measured the transcript expression levels of 8 anti-bacterial and 8 anti-viral putative biomarker genes, and the innate (leukocyte respiratory burst, plasma lysozyme activity and hemolytic activity of the alternative complement pathway) and cellular (relative number of erythrocytes, lymphocytes and thrombocytes, and granulocytes such as monocytes and neutrophils) responses to these challenges. Overall, we only found a few minor effects of either tetracycline or florfenicol on immune gene expression or function at either temperature. Although several studies have reported that antibiotics may negatively affect fish immune responses, our results show that industry-relevant dietary tetracycline and florfenicol treatments do not substantially impact the salmon's innate immune responses. Currently, this is the most comprehensive study on the effects of antibiotics administrated according to industry protocols on immune function in Atlantic salmon. Highlights: Salmon were acclimated to 12 and 20 °C and fed with tetracycline or florfenicol. Fish were immune stimulated with bacterial or viral antigens. Transcript expression levels of anti-bacterial and anti-viral biomarkers were largely unaffected by either tetracycline or florfenicol treatment at 12 or 20 °C. Innate and cellular immune responses were also not affected by these antibiotics at either temperature.